A Patient Navigator Intervention Supporting Timely Transfer Care of Adolescent and Young Adults of Hispanic Descents Attending an Urban Primary Care Pediatrics Clinic. Issue 2 (10th March 2021) - Allende-Richter, Sophie; Glidden, Patricia; Maloyan, Mariam; Khoury, Zana; Ramirez, Melanie; O'Hare, Kitty
Abstract : Supplemental Digital Content is available in the text. Abstract : Introduction: While comprehensive health care transition is associated with better health outcomes, navigating health care transition can be difficult for adolescents and young adults (AYAs), especially those with fewer resources. Our practice serves low-income patients from birth to their 26th birthday; many are medically and socially complex and experience several obstacles to navigate care. As a result, most have not initiated a transfer to adult medicine by age 25. This quality-improvement initiative was designed to implement a structured intervention that supports the planned transfer of care to adult primary care. Methods: Informed by our baseline data on all patients eligible to transfer care, we designed a patient outreach workflow centered on a patient navigator (PN) intervention. We used a Plan-Do-Study-Act format to optimize our process and run charts to evaluate our intervention. Results: Over 3 years, our PN reached out to 96% of patients (n = 226) eligible to transfer care and offered transfer assistance in person or in writing. Among those surveyed, 92% (n = 93) reported awareness of our practice transition policy, and 83% (n = 64) rated their confidence to transfer care at 3 or higher on a 5-point scale. Conclusions: AYAs are aware of our practice transition policy, yet they welcome in-person transfer assistance. This intervention seems to improve their confidence to transfer care. However, despite PN outreach efforts, many remain empaneled in our practice and thus lack the self-care skills necessary to complete the transfer independently. Future transition interventions should address AYA's self-management skills toward transition readiness.